3D-QSAR CoMFA and CoMSIA Study on Benzodipyrazoles as Cyclin Dependent Kinase 2 Inhibitors - Dessalew, Nigus; Singh, Sanjeev K. (Medicinal Chemistry, 2008)
Cyclin dependent kinase 2 (CDK2) has appeared as an important drug target over the years with a multitude of therapeutic potentials. With the intention of designing compounds with enhanced inhibitory potencies against CDK2, the 3D-QSAR CoMFA and CoMSIA study on benzodipyrazoles series is presented here. The developed models showed a strong correlative and predictive capability having a cross validated correlation co-efficient of (r2 cv) 0.699 for CoMFA and 0.794 for CoMSIA models. A very good conventional and predicted correlation co-efficients were also obtained: CoMFA (r2 ncv, r2 pred: 0.883, 0.754), CoMSIA (0.937, 0.815). The models were found to be statistically robust and are expected to be of an aid to design and/or prioritize drug likes for synthesis.
Keywords: CDK2